Green Banking in Bangladesh: A Commitment towards the Global Initiatives (Journal of Business and Technology (Dhaka), 2014)
Banks usually provide dedicated public services for profits. It is believed that profit should not be earned at the expense of the world's most pressing environmental problems. Thus the concept of green banking is evolved in response to the global initiative to save environment. It is a kind of welfare banking for the society at large, it responses to be green in daily operations and financing of nature conservation projects. The present paper aims to highlight the green banking road map in Bangladesh and the status of its implementation. Further, an attempt has been made to explore activities of commercial banks in comparison with global green banking initiatives. The study utilized secondary data available from related websites, published reports and articles. The study concluded that Bangladesh is far behind their counterparts from the developed countries. But the general picture presents a transition to green banking in a consistent manner for most banks. By taking care of its infrastructure development and accelerating its existing green movements, banks can ensure sustainability for itself and greener world for communities. DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18284 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 17-40